Pengaruhi Mahasiswa Akuntansi Memilih Enterpreneuship Dengan Menggunakan TPB Di Universitas Medan - Vina Arnita; Handriyani Dwilita (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study examines whether the factors that influence accounting students become entrepreneurs at Panca Budi Development University using the theory of planned behavior. The variables that influence are the influence of independent attitude, the influence of motivation, student's interest in entrepreneurship at the University of Development Panca Budi Medan. Then the data obtained were analyzed using multiple regression analysis, data normality test, multicollinearity test and heterokedasticity test. The method used is a factor analysis test by looking at the effect of each variable.In this study using the theory of planned behavior to see accounting students choose to become entrepreneurs. The results of this study are the existence of a high influence on the three variables using the Planned Behavior theory of accounting students to become entrepreneurs. The influence of the three variables tends to influence students choosing to become entrepreneurs. This phenomenon occurs because many cafes or beverage shops are circulating in the city of Medan. This happens because the opportunity to become an entrepreneur is very large and the owner of the cafe or shop is a student who is in college or has finished college. With a cafe that has sprung up so as to create jobs for students who are in college or who are on an internship